2020
DOI: 10.1101/2020.05.13.095091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of the conserved Alveolate kinase MAPK2 decouplesToxoplasmacell growth from the cell cycle

Abstract: Mitogen-activated protein kinases (MAPKs) are a conserved family of protein kinases that regulate signal transduction, proliferation, and development throughout eukaryotes. The Apicomplexan parasite Toxoplasma gondii expresses three MAPKs. Two of these, ERK7 and MAPKL1, have been respectively implicated in the regulation of conoid biogenesis and centrosome duplication. The third kinase, MAPK2, is specific to and conserved throughout Alveolata, though its function is unknown. We used the auxin-inducible degron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Other phenotypes included abnormalities in parasite morphology. Multiple genes displayed defects similar to those previously observed for TgMAPK-L1 and TgMAPK2 57 60 . Aberrant morphologies allude to failures in daughter cell assembly or cytokinesis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Other phenotypes included abnormalities in parasite morphology. Multiple genes displayed defects similar to those previously observed for TgMAPK-L1 and TgMAPK2 57 60 . Aberrant morphologies allude to failures in daughter cell assembly or cytokinesis.…”
Section: Discussionsupporting
confidence: 82%
“…TgMAPK-L1 displayed cell cycle–dependent localization to diffuse puncta, consistent with its localization to the pericentrosomal matrix. In addition to the reported cytosolic localization 60 , TgMAPK2 was observed at paired puncta in a subset of vacuoles, shedding additional light into the function of this kinase.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…A major advantage of this system is the rapid degradation of the targeted protein and its reversibility. Indeed, several studies have shown that phenotypes caused by the depletion of a targeted protein can be reversed by simply washing out auxin from the culture media (Hu et al, 2020;Khelifa et al, 2021). The AID system can also be used in vivo in mice, although in this case auxin needs to be provided by oral gavage and in the drinking water .…”
Section: The Auxin-inducible Degron Systemmentioning
confidence: 99%
“…The proper division of the centrosome is regulated by TgCDPK7 6 , TgMAPK-L1 7 and TgMAPK2 8 . Moreover, cell division of the T. gondii tachyzoite is regulated by five cyclically expressed kinases denoted as TgCrks; these kinases control several cell cycle checkpoints and ensure the (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%